Development of Student Worksheets Based on Higher Order Thinking Skills Based on Assessment Culture and Student's Productive Disposition - Nurul Ulfa Sholihah; Supratman; Sri Tirto Madawistama (Jurnal Ar Ro'is Mandalika (Armada), 2026)
This research and development (R&D) study aimed to develop Higher Order Thinking Skills (HOTS)-based student worksheets (LKPD) grounded in assessment culture and productive disposition. Following the ADDIE model (Analyze, Design, Develop, Implement and Evaluate). The study involved three mathematics teacher, five students for preliminary analysis, two subject matter experts, two media experts and 25 students for implementation. Data were collected through unstructed interviews and several instrument such as an assessment culture questionnaire, a productive disposition questionnaire, expert validation sheets and user response questionnaire. Findings showed that the student’s assessment was categorized as “compliance”, and their productive disposition was “moderate”. The worksheets were validated as “highly feasible” by experts and received “very good” user feedback. Furthermore, an 84% student mastery rate in the competency test demostrates the effectiveness of the developed HOTS based worksheet for learning.